The effect of youths as change agents on self-rated health status and happiness among adult neighbors: a cluster randomized controlled trial in Sri Lanka - Islam, Zobida; Mizoue, Tetsuya; Chandraratne, Nadeeka; Indrawansa, Susantha; Gunawardena, Nalika (Frontiers in Public Health, 2025)
BackgroundLifestyle modification intervention may influence the mental health of the participants. The present study examined the effect of youth-led interventions on self-rated health (SRH) and happiness among community adults in Sri Lanka.MethodsThis cluster-randomized controlled trial study was conducted in a semi-urban area of Colombo in Sri Lanka. Out of 68 Grama Niladari (GN) divisions in the selected Divisional Secretariat, 24 GN (intervention = 12 and control = 12) were randomly selected. The intervention group received health education from their community’s young adults (aged 15–29 years) to identify and modify the determinants of their undesired health behaviors twice a month. The control group received no intervention. At baseline and at 12-month follow-up surveys, participants were asked to rate their SRH and happiness using a single-question measure. Multilevel logistic and multilevel linear regression models were used to assess the effects of the intervention on changes in binary and continuous SRH and happiness, respectively, from baseline to end line.ResultsAt the 12-month follow-up, 483 adults aged 27 to 65 years (intervention = 245; control = 238) completed the final assessments out of the 512 participants enrolled at baseline. Participants in the intervention group showed higher odds of achieving good SRH [odds ratio (OR) 1.85, 95% confidence interval (CI) 1.18–2.90] compared to those in the control group. They showed a significantly greater change in SRH than controls; the mean difference in SRH change between the two groups was 0.13 (95% CI, 0.002–0.26). There was no significant difference in happiness between the two groups; the OR (95% CI) was 1.37 (0.85–2.22) for the intervention group.ConclusionThe results suggest that a youth-led educational program promoting healthier behaviors among their neighbors can effectively improve the SRH of community adults in a semi-urban area of Colombo, Sri Lanka.Clinical trial registrationhttps://slctr.lk/trials/slctr-2017-002, SLCTR/2017/002.